Analysis of Numeration Literacy Program Implementation In Low Class Learning - Muhammad Misbahudholam AR; Zainuddin Zainuddin; Kurratul Aini; Tuti Mutia (Universitas Muhammadiyah Enrekang, 2022)
This study aims to describe (1) the implementation of numeracy literacy implementation of low-grade students of SDN Batuan I, (2) constraints on the implementation of numeracy literacy of low-grade students of SDN Batuan I, (3) efforts made to overcome obstacles in the implementation of the numeracy literacy program at SDN Batuan I. This research is a qualitative research with a case study approach. Data collection was carried out by observation, interviews and documentation as primary data and some secondary data in the form of references used. The results showed that (1) the application of the numeracy literacy program in low-grade learning at SDN Batuan I was running well and effectively. This is evidenced by the existence of reading and memorizing formulas in the form of singing, there is a reading corner and a reading garden, there is a literacy tree, and there is a school library; (2) obstacles in the implementation of numeracy literacy for low-grade students of SDN Batuan I, namely differences in the background and role of parents, book eligibility, and motivation levels for literacy program targets; (3) efforts made to minimize obstacles during the implementation of the numeracy literacy program, namely communication renewal, strategies to increase interest in reading that are appropriately adapted to student conditions and improving the quality of literacy program targets through training organized by schools.